Staphylococcus aureus sebagai agen penyebab infeksi pada kasus erisipelas kruris dekstra dengan liken simpleks kronikus - Anak Agung Indah Jayanthi; Ni Made Adi Tarini; I Gusti Ayu Agung Praharsini (Intisari Sains Medis, 2020)
Background: Erysipelas is a skin and soft tissue infection that affects the epidermis and superficial dermis as well as superficial lymphatic vessels. Erysipelas can occur due to the entry of bacteria through the skin barrier that is not intact and can occur in other medical conditions such as in patients with lichen simplex chronicus.Case presentation: A man, aged 62, Javanese, came to the Sanglah Hospital Emergency Room because of swelling, redness, and pain in the right calf since 2 days ago and complained of itching in the right lower leg since 1 week ago. The patient has a 1-year history of lichen simplex chronicus and has received medication. Physical examination found the presence of erythema patch efflorescence, warm palpation of the touch, non-pitting edema, pain on pressure, and diascopy test of blanching on pressure. The results of the wound bed culture examination showed the isolation of S. aureus. Intravenous fluids, open compresses, antibiotics, pain relievers, and anti-inflammatory creams were given to patients who experienced improvement on day 8.Discussion: The diagnosis of erysipelas is determined from the patient's complaints and the clinical picture from the results of the physical examination. In erysipelas, microbial pathogens enter through skin damage, then spread locally and systemically. Antibiotics have become the standard in the management of erysipelas by bacterial infections. The administration of ceftriaxone antibiotics was carried out based on the results of the sensitivity test also obtained on the results of the isolation of sensitive S. aureus bacteria.Conclusion: Diagnosis of erysipelas is based on history, physical examination, and investigation. Management of patients includes open compresses, administration of fluids, antibiotics, pain relief, and use of anti-inflammatory creams.